Radical innovation and value extraction: the role of the user's entrepreneurial passion on satisfaction with product, firm, and industry. (4th March 2017) - Turner, Tobin; Hendry, Stuart
Abstract : While innovation has long been considered central to firms creating a sustainable competitive advantage, researchers have had difficulty in establishing empirical links between innovation and improved customer satisfaction or firm performance. In this study we find empirical support that individuals exhibiting entrepreneurial passion (EP) value innovation differently than those without EP. In contrast to those without EP, innovation-users with EP attribute the value of an innovation to an innovated product rather than to the company or industry. We also find that there is the potential for customers' firm-level satisfaction to leak from the firm to the overall industry. This study offers insights into why innovators often fail to extract customer value as anticipated. Recognizing entrepreneurial passion, consequently, matters both for entrepreneurs and their customers.